2011
DOI: 10.1111/j.1365-2141.2011.08871.x
|View full text |Cite
|
Sign up to set email alerts
|

Management of osteonecrosis in children and young adults with acute lymphoblastic leukaemia

Abstract: Summary Osteonecrosis is a disabling complication in children and young adults with acute lymphoblastic leukaemia. It can affect any or multiple joints but the hip and knee are most frequently involved and a cause of long‐term disability. The problem is almost exclusively that of older children and young adults of whom over 70% have asymptomatic changes on screening magnetic resonance imaging and 15–20% have resulting symptoms. Dexamethasone is associated with a higher risk than prednisolone in US but not Euro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 103 publications
(155 reference statements)
2
40
0
1
Order By: Relevance
“…We demonstrate that pretreatment with H1 receptor antagonists, PAF receptor antagonist, or dexamethasone can all partially mitigate the severity of asparaginase-induced allergic reactions to a similar extent; however, only dexamethasone was able to partially maintain plasma asparaginase activity. This may be particularly important for selecting a pretreatment agent in patients that are at a high risk of developing glucocorticoid-induced osteonecrosis (Vora, 2011). Our results also support the need for a clinically available PAF receptor antagonist for mitigating immune responses (Roberts et al, 1988;Hozawa et al, 1995;Kingsnorth et al, 1995) and emphasize that it may be important to monitor asparaginase activity if pretreatment medications are used.…”
Section: Model Of Asparaginase Allergysupporting
confidence: 70%
“…We demonstrate that pretreatment with H1 receptor antagonists, PAF receptor antagonist, or dexamethasone can all partially mitigate the severity of asparaginase-induced allergic reactions to a similar extent; however, only dexamethasone was able to partially maintain plasma asparaginase activity. This may be particularly important for selecting a pretreatment agent in patients that are at a high risk of developing glucocorticoid-induced osteonecrosis (Vora, 2011). Our results also support the need for a clinically available PAF receptor antagonist for mitigating immune responses (Roberts et al, 1988;Hozawa et al, 1995;Kingsnorth et al, 1995) and emphasize that it may be important to monitor asparaginase activity if pretreatment medications are used.…”
Section: Model Of Asparaginase Allergysupporting
confidence: 70%
“…Candidate-gene studies have implicated inherited variation in PAI-I, TYMS, VDR, and factor V Leiden in the risk of osteonecrosis among patients with ALL. [74][75][76][77][78][79] A GWAS has implicated ACP1 and genes related not only to osteonecrosis but also to hypoalbuminemia and hypercholesterolemia (supportive of a role for drug-induced lipidemias) as contributors to osteonecrosis risk. 80 Additional genome-wide studies for osteonecrosis risk in the setting of differing age groups and differing ALL therapeutic protocols are needed to define genetics of this disorder.…”
Section: Glucocorticoidsmentioning
confidence: 99%
“…19 Although some components of antileukemic treatment, especially glucocorticoids, are considered to play a critical role in the etiology of osteonecrosis, the pathogenesis is not fully understood. 20 We and others have shown that BMD is already low when ALL is diagnosed, and that the final BMD loss at cessation of ALL treatment is mainly determined by BMD values at the start of treatment. 17,21,22 This suggests that the disease itself and genetic variation in genes that influence bone density may be important risk factors for BMD loss.…”
Section: Introductionmentioning
confidence: 92%
“…10 Low BMD values were still present 1 year after cessation of treatment in patients who had ON, even though some patients have radiological and clinical improvement of ON. 20 This is not surprising, as the effect of avoidance of weight-bearing activities for several months is likely to continue after cessation of treatment. Previous studies have shown that bone loss or its destruction can recover, although the recovery process is slow 49 and during this period there may be a high risk of fractures.…”
Section: B Amentioning
confidence: 99%